The use of hormonal contraception and breast cancer - Dwi Wahyuning Anggarini; Anita Rahmawati; Margono Margono (Jurnal Kesehatan Ibu dan Anak, 2018)
The prevalence of breast cancer continues to increase in the world, including in Indonesia. The main factor causing breast cancer is not yet known certainly. The research was conducted to determine the correlation between hormonal contraceptive use and the prevalence of breast cancer. The research design was case control. The sampling technique used purposive sampling. The number of samples was 85 cases and 85 controls. The case group was women with breast cancer at RSUP Dr. Sardjito Yogyakarta in 2017. The control group was a woman who checked herself in Obsgyn RSUP Dr. Sardjito in 2017 who was not breast cancer and other cancers. The data collected through secondary data was taken from medical records. The analysis was done using Chi-square test and logistic regression. There was a significant correlation between hormonal contraceptive use and breast cancer prevalence p-value = 0.004 OR = 2.378 (95% CI 1.2282-4.412). The use of hormonal contraception increased the risk of breast cancer prevalence by 2.378 times. Other risk factors were found at age 40 years old p-value = 0.002 OR = 2.641 (95% CI 1.416-4.925), age of menarche <12 years p-value = 0.004 OR = 2.868 (95% CI 1.366-6.021), obesity p-value = 0.002 OR = 2.875 (95% CI 1.434-5.765), and nullipara p-value = 0.005 OR = 4.000 (95% CI 1.402-11.410). The suggestion was that midwives and prospective acceptors/acceptors of family planning pay attention to the risk factors for hormonal contraceptive use on breast cancer prevalence and other risk factors that affected breast cancer.